Discussion of the operating range of frequency modulated radars in the presence of interference. Issue 3 (June 2014) - Berroth, Manfred; Jacob, Arne F.; Schmidt, Lorenz-Peter; Schipper, Tom; Harter, Marlene; Mahler, Tobias; Kern, Oliver; Zwick, Thomas
<x content-type="archive" xml:space="preserve">Abstract</x> This paper discusses the operating range of frequency modulated (FM) radars in the presence of interference. For this purpose, radar- and path loss equations are used to draw the equipotential lines for a given signal-to-interference ratio as a function of the spatial distribution of targets and interferers in order to identify relevant scenario constellations. Further the factors influencing the gain of signal versus deterministic interference are discussed based on measurements and simulations. Finally, the influence of different kinds of interference on the spectrum of a frequency modulated continuous wave radar is shown.